Comparison of sensitivity of lung ultrasound and chest x-ray imaging for the diagnosis of community-acquired pneumonia in children: Primerjava občutljivosti ultrazvoka in rentgenskega slikanja pljuč za diagnosticiranje zunajbolnišnične pljučnice pri otrocih - Berce, Vojko (Acta Medico-Biotechnica, 2021)
Purpose: Lung ultrasound (LUS) has only recently been considered to be a suitable tool for diagnosing community acquired pneumonia (CAP) in children. Little is known about the usefulness of LUS in different types of pneumonia. Therefore, we analyzed and compared the sensitivity of chest X-ray (CXR) and LUS in different etiological types of CAP in children.Methods: We performed a prospective study in 166 children with CAP, who were admitted to the hospital. The participants were stratified into bacterial (n=80), atypical bacterial (n=32) and viral (n=54) pneumonia subgroups, according to the laboratory and microbiological results. LUS and CXR were performed on all patients at admission.Results: Pneumonia was detected with LUS in 161 (97.0%) participants and with CXR in 137 (82.5%) participants (p
Keywords: lung ultrasound; community acquired pneumonia; etiology; children